Systemic risk of maritime-related oil spills viewed from an Arctic and insurance perspective. (1st September 2019) - Johannsdottir, Lara; Cook, David
Abstract: There is a wish for economic development in the Arctic, especially in relation to the region's untapped marine and hydrocarbon resources. However, such developments are inherently risky, entailing the possibility of trade-offs and potentially jeopardizing a fragile and pristine natural environment which provides multiple sources of well-being to the Arctic's four million inhabitants. When the risks of economic development are evaluated, they are usually assessed on a micro (enterprise risk) and/or meso level (portfolio risk, such as an industry). Systemic risk is considered to a much lesser degree. There is also limited discussion about mitigation methods, including the role of insurance in dealing with the consequences of failures, such as oil spills. The aim of this study is, therefore, to explore the systemic risk of maritime-related oil spills in general and place the findings in an Arctic and insurance perspective. The study is based on secondary data relating to major maritime-related oil spills from drilling and shipping. Two analytical frameworks were employed, one explaining the scaling of risks, and another showing the interplay between subsistence and monetized economies in tandem with their institutional, environmental, social and cultural context. The findings suggest, if the worst-case scenario materializes, that maritime-related oil spills may have social/cultural, environmental, and economic impacts, in addition to security/policy implications, as well as affecting businesses involved in the disaster and their partners. This study has academic implications since there are, so far, limited studies carried out on systemic-level risk, but it also has policy relevance, for instance for local and regional authorities and international bodies, such as the Arctic Council, in terms of holistic risk-assessment and its recommended use of appropriate decision-making and evaluative frameworks such as ecosystem-based management. Highlights: Systemic risk is seldom evaluated when risks of economic development are evaluated. Economic developments in the Arctic expected to increase likelihood of oil spills. Opportunity in market economy may be risk in the subsidence economy, or vice versa. Oil spills may have social, environmental, economic, security and business impacts. Insurance sector is already recognizing the characteristics of systemic risks.